3βHSD and CYB5A double positive adrenocortical cells during adrenal development/aging - Nakamura, Yasuhiro (Endocr Res, 2014)
Androstenedione is a common precursor of sex steroids produced and secreted in the human adrenal gland and produced by 3β-hydroxysteroid dehydrogenase (3βHSD), 17α-hydroxylase/17-20 lyase (CYP17) and cytochrome b5 (CYB5A). 3βHSD is expressed in the zona glomerulosa (ZG) and fasciculata (ZF), CYP17 in the ZF and zona reticularis (ZR) and CYB5A in the ZR, respectively. We previously demonstrated the presence of cortical parenchymal cells co-expressing 3βHSD and CYB5A with hybrid features of both ZF and ZR in human adrenal cortex and hypothesized that these cells may play an important role in androstenedione production in human adrenal gland. Age-related morphologic development of these hybrid cells has, however, not been studied. Therefore, in this study, 48 human adrenal specimens from various age groups were retrieved. Double-immunohistochemical analyses were used in order to study the correlation between this hybrid cell type and age. In both male and female adrenal cortex, the mean of total adrenocortical area, the area of CYB5A positive cells and the mean of its ratio reached highest peak in the 21–40 year-old (y.o.). The greatest overlap between 3βHSD and CYB5A in both total and relative area was present in the 13–20 y.o. group. For all of the markers above, statistically significant differences were detected among the different age groups examined (P<0.05). These findings all indicated that both area and ratio of 3βHSD and CYB5A double positive cells, which could represent the hybrid cells of ZF and ZR, are correlated with human adrenal development and could subsequently influence age-related serum androstenedione levels.